DEVELOPMENT MOLECULAR IMPRINTED POLYMER SOLID PHASE EXTRACTION FOR SEPARATION NITROFURANTOIN RESIDUE IN CHICKEN EGGS - Gunawan, Untung
The use of nitrofurantoin and other nitrofuran antibiotics to cure infected animals in Indonesia is limited because of its tendency to be carcinogenic and mutagenic. Recent studies show that nitrofurantoin are still used in several farms, ,the residues may exist in eggs. Various methods for analysis of residues of nitrofurantoin have been developed. One of, the commonly used methods is (HPLC) with Mass Spectrometry detector (MS). However, the availability of the instrument in laboratory is limited due to high cost. Therefore, development of HPLC method with Ultraviolet (UV) detector is necessary. However, it is necessary to separate the matrix prior to the analysis. Molecular Imprinted Polymers (MIP) is widely developed due to its selectivity. The purposes of this study were to obtain valid analytical method for nitrofurantoin and obtain selective MISPE for the separation of nitrofurantoin residues in chicken eggs. Analytical methods development of nitrofurantoin included optimization of HPLC system, System Suitability Test (SST) and validation of analytical methods In silico study was used for MIP design by observing the difference of Gibbs free energy using Gaussian 09 software with Density Functional Theory methods (DFT) using 6-31 IG as basis set. MIP synthesis was carried out using bulk method with nitrofurantoin as template, acrylamide as functional monomer, ethyleneglycoldimethacrylate (EGDMA) as crosslinker, azobisisobutyronitrile (AIBN) as initiator reaction and dimethylformanmide (DMF) as solvent. Molecular Imprinted Solid Phase Extraction (MISPE) was prepared by insert MIP into SPE cartridge. Non Imprinted Solid Phase Extraction (NiSPE) was prepared as comparative. Synthesized MISPE was characterized and compared to NISPE and Solid Phase Extraction (SPE) CIS on the market. Characterized MISPE was used for analysis of eggs samples on the market. Analytical method development provided a good linearity with 12 0.9999, Vxo 0.7066 %, accurgcy with % recovery of 98.98 100.69 %, precision with coefficient of variance of 0.4650 %, limit of detection of 1.1990 gg/mL, and limit of quantification of 3,6340 ug/mL. Acrylamide was used as functional monomer with Gibbs enery value of -324137 kcal/mol. The recovery of